Coming Out to Play: Privacy, Data Protection, Children’s Health, and COVID-19 Research - Beauvais, Michael J. S.; Knoppers, Bartha Maria (Frontiers in Genetics, 2021)
The COVID-19 pandemic has underscored the need for new ways of thinking about data protection. This is especially so in the case of health research with children. The responsible use of children’s data plays a key role in promoting children’s well-being and securing their right to health and to privacy. In this article, we contend that a contextual approach that appropriately balances children’s legal and moral rights and interests is needed when thinking about data protection issues with children. We examine three issues in health research through a child-focused lens: consent to data processing, data retention, and data protection impact assessments. We show that these issues present distinctive concerns for children and that the General Data Protection Regulation provides few bright-line rules. We contend that there is an opportunity for creative approaches to children’s data protection when child-specific principles, such as the best interests of the child and the child’s right to be heard, are put into dialogue with the structure and logic of data protection law.